STUDI HABITAT PELANDUK (Tragulus sp) DALAM KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - hajiah, Nur; Nurdjali, Bachrun; anto, Eri (Universitas Tanjungpura, 2013)
Forest is natural resource which is provide great benefit to human welfare, both perceived benefit directly or indirectly, forest has potential and function to maintain the environmental balance. Pelanduk (Tragulus sp) is one of the endangered species due to poaching and clearing of forest areas used for farming communities which causing loss of vegetation, loss of habitat and food sources for the pelanduk (Tragulus sp). The objective of this study is to find out pelanduk (Tragulus sp) habitat in protected areas of Ambawang Montain. This study was conducted using squares method by double plot and the laying of the first plot is conducted purposively. The observation plot is in shape of square 20 m x 20 m with 20 m spacing between plots systematically. The number of plots for the primary forest, secondary forest and community garden is 27 plots. The factors that were analyzed in this study were water, soil, air humidity, temperature and the vegetation of pelanduk (Tragulus sp). The highest INP was in the societys rubber plantation with INP 286,5911 %. Based on analisyis, the most preferred food by pelanduk (Tragulus sp) is simpur. The pandanus forest and resam is the best shelter for the pelanduk (Tragulus sp) and some of them are using the buttresses-tree. The analisyis of water shows that the water is still proper to use as a source of drinking water for the pelanduk (Tragulus sp). And based on the measurement of temperature and humidity, it is still appropriate to the existence of pelanduk (Tragulus sp). Key words : Habitat, Pelanduk (Tragulus sp), Protected forest